2015
DOI: 10.2466/04.17.cp.4.15
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Northeast Asians Win So Few Nobel Prizes?

Abstract: Most scientifi c discoveries have originated from Europe, and Europeans have won 20 times more Nobel Prizes than have Northeast Asians. We argue that this is explained not by IQ, but by interracial personality diff erences, underpinned by diff erences in gene distribution. In particular, the variance in scientifi c achievement is explained by diff erences in inquisitiveness (DRD4 7-repeat), psychological stability (5HTTLPR long form), and individualism (mu-opioid receptor gene; OPRM1 G allele ). Northeast Asia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…These findings might contribute to explaining the current global distribution of scientific discoveries and Nobel prizes (Murray, ) and can be added to a range of other explanations in the literature that have been advanced to explain this phenomenon, such as national‐level differences in general scientific curiosity (Kura et al., ), or personality profiles related to scientific discoveries (Dutton et al., ). Note that these alternative explanations are not inconsistent with the androgen hypothesis, as androgen levels are related to personality traits (e.g., Herbert, ; Zuckerman, ).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…These findings might contribute to explaining the current global distribution of scientific discoveries and Nobel prizes (Murray, ) and can be added to a range of other explanations in the literature that have been advanced to explain this phenomenon, such as national‐level differences in general scientific curiosity (Kura et al., ), or personality profiles related to scientific discoveries (Dutton et al., ). Note that these alternative explanations are not inconsistent with the androgen hypothesis, as androgen levels are related to personality traits (e.g., Herbert, ; Zuckerman, ).…”
Section: Discussionmentioning
confidence: 81%
“…Note that these alternative explanations are not inconsistent with the androgen hypothesis, as androgen levels are related to personality traits (e.g., Herbert, 2015;Zuckerman, 2013). Thus, androgen levels may possibly be one of the more fundamental causes for differences in traits as described in previous research Kura et al, 2015). This is further supported by a large body of research showing that androgens such as testosterone are associated with status seeking and competitiveness (see Herbert, 2015, for a review).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Though results of studies that have administered the Kirton's Adaptation-Innovation Inventory on Asian samples suggest that Asia may not be as deficient in innovative individuals as depicted (e.g., Ee et al, 2007), studies have shown that Asians tend to possess lower levels of psychological traits predictive of exceptional scientific accomplishments (e.g., inquisitiveness) and that this seems to stem from genetic bases (e.g., Kura et al, 2015). This is in addition to the studies cited by Kanazawa (2006) showing how environmental factors specific to Asia, such as its educational systems, may serve to discourage creative thinking.…”
Section: Creativity Of Asiansmentioning
confidence: 99%
“…Although this is beyond the borders of our study, it may be noted that relatively high IQ, wealthy countries with low levels of per capita science Nobel prize achievement-notably Japan, South Korea, and Finland-have been subject to similar selection pressures. They are adapted to an ecology of extreme harshness and also predictability (see Kura, te Nijenhuis & Dutton, 2015;Rushton, 1995), with Finnsthough not Finland-Swedes to the same degree-having as much as 10% East Asian admixture (Virtaranta-Knowles et al, 1991). It is possible that this would very strongly select for highly cooperative groups, meaning it would select against low empathy and reduce testosterone (as a predictor of aggression and a correlate of low empathy) ( Baron-Cohen, 2002).…”
Section: Introductionmentioning
confidence: 99%